Antioxidant protection enzyme activity in the blood serum and large intestinal mucosa of rats with prolonged gastric hypochlorhydria and given multiprobiotics - Pylypenko, S. V.; Koval, A. A. (Regulatory Mechanisms in Biosystems, 2019)
The activity of antioxidant protection enzymes in the blood serum and colon mucosa in rats was studied under the conditions of 28-days administration of omeprazole on its own and omeprazole together with multiprobiotics "Symbiter" and "Apibact". Physiological and biochemical study methods were applied. It was found that after omeprazole administration, the activity of superoxide dismutase in the blood serum decreased, and the activity of catalase increased compared to the control. With the co-administration of omeprazole and multiprobiotics, the activity of superoxide dismutase increased compared to the group of rats that received omeprazole only during the same time, but remained less compared to the control group. The content of reduced glutathione in the blood serum of rats after administration of omeprazole decreased, the activity of glutathione peroxidase and glutathione transferase increased, and the activity of glutathione reductase decreased compared to the control. With co-administration of omeprazole and multiprobiotics, the serum RG content was at the control level, the activity of glutathione reductase exceeded the control values. The activity of glutathione reductase decreased compared to the group receiving omeprazole only. The activity of glutathione reductase increased and did not differ from the control values. In the colon mucosa, superoxide dismutase and catalase activity decreased compared to control. With the combined administration of omeprazole and multiprobiotics, superoxide dismutase and catalase activity increased and even exceeded the control values. With the administration of omeprazole, the reduced glutathione content in the colon mucosa was lower than that in the control. The activity of glutathione peroxidase increased and glutathione transferase and activity of glutathione reductase decreased compared to the control. With co-administration of omeprazole and multiprobiotics to rats, the reduced glutathione content increased compared to the group of rats administered omeprazole only, and even exceeded that in the control.